An efficient multi–objective evolutionary algorithm for energy–aware QoS routing in wireless sensor network. (1st August 2013) - Su, Sheng; Yu, Haijie; Wu, Zhenghua
A multi–objective evolutionary algorithm is proposed to solve the routing problem in wireless sensor network. Two performance metrics, which consist of the maximisation of remaining lifetime of the wireless sensor network and the minimisation of transmission delay, are considered. Dominating relationship and similarity between solutions are used to compute the fitness of a solution in a population. An energy–saving combination operator executed independently by sink node is presented to create new solutions. An exploitation operator and exploration operator are investigated to find better solutions at the neighbour of a solution space and to inject new genes into a population, respectively. Simulation experiments show that our multi–objective routing evolutionary algorithm (MOREA) is better in solution quality and computational efficiency than the up–to–date ant colony optimisation routing algorithm (ACOR). The non–dominated solutions of MOREA can totally dominate those of ACOR. Moreover, MOREA is several ten times faster than ACOR.